The effect of saponins from Ampelozizyphus amazonicus Ducke on the renal Na+ pumps' activities and urinary excretion of natriuretic peptides - Diniz Lúcio Ricardo; Portella Viviane; Cardoso Flávia; de Souza Aloa; Caruso-Neves Celso; Cassali Geovanni; dos Reis Adelina; Brandão MariadasGraçasLins; Vieira Maria Aparecida (BMC, 2012)
Abstract Background In a previous study, we showed that a saponin mixture isolated from the roots of Ampelozizyphus amazonicus Ducke (SAPAaD) reduces urine excretion in rats that were given an oral loading of 0.9 % NaCl (4 ml/100 g body weight). In the present study, we investigated whether atrial natriuretic peptides (ANP) and renal ATPases play a role in the SAPAaD- induced antidiuresis in rats. Methods To evaluate the effect of SAPAaD on furosemide-induced diuresis, Wistar rats (250-300 g) were given an oral loading of physiological solution (0.9 % NaCl, 4 ml/100 g body weight) to impose a uniform water and salt state. The solution containing furosemide (Furo, 13 mg/kg) was given 30 min after rats were orally treated with 50 mg/kg SAPAaD (SAPAaD + Furo) or 0.5 ml of 0.9 % NaCl (NaCl + Furo). In the SAPAaD + NaCl group, rats were pretreated with SAPAaD and 30 min later they received the oral loading of physiological solution. Animals were individually housed in metabolic cages, and urine volume was measured every 30 min throughout the experiment (3 h). To investigate the role of ANP and renal Na+ pumps on antidiuretic effects promoted by SAPAaD, rats were given the physiological solution (as above) containing SAPAaD (50 mg/kg). After 90 min, samples of urine and blood from the last 30 min were collected. Kidneys and atria were also removed after previous anesthesia. ANP was measured by radioimmunoassay (RIA) and renal cortical activities of Na+- and (Na+,K+)-ATPases were calculated from the difference between the [32P] Pi released in the absence and presence of 1 mM furosemide/2 mM ouabain and in the absence and presence of 1 mM ouabain, respectively. Results It was observed that SAPAaD inhibited furosemide-induced diuresis (at 90 min: from 10.0 ± 1.0 mL, NaCl + Furo group, n = 5, to 5.9 ± 1.0 mL, SAPAaD + Furo group n = 5, p < 0.05), increased both Na+-ATPase (from 25.0 ± 5.9 nmol Pi.mg-1.min-1, control, to 52.7 ± 8.9 nmol Pi.mg-1.min-1, p < 0.05) and (Na+,K+)-ATPase (from 47.8 ± 13.3 nmol Pi.mg-1.min-1, control, to 79.8 ± 6.9 nmol Pi .mg-1.min-1, p < 0.05) activities in the renal cortex. SAPAaD also lowered urine ANP (from 792 ± 132 pg/mL, control, to 299 ± 88 pg/mL, p < 0.01) and had no effect on plasma or atrial ANP. Conclusion We concluded that the SAPAaD antidiuretic effect may be due to an increase in the renal activities of Na+- and (Na+,K+)-ATPases and/or a decrease in the renal ANP.